Interrogating glacier mass balance response to climatic change since the Little Ice Age: reconstructions for the Jotunheimen region, southern Norway. (15th October 2021) - Hiemstra, John F.; Young, Giles H. F.; Loader, Neil J.; Gordon, Penny R.
Abstract : Developing a long‐term understanding of the cryosphere is important in the study of past climatic change. Here we used a nested approach combining diverse instrumental (monthly meteorological data from four weather stations, as well as gridded data) and proxy data (based on blue intensity measurements from local tree ring records) to create a reconstruction of past summer temperature for the central Jotunheimen area in southern Norway. This record was then used to reconstruct annual glacier mass balance from 1962, the start of the yearly measurements, back to 1722, immediately prior to the regional Little Ice Age maximum. Our reconstruction of the 'average' Jotunheimen cumulative glacier mass balance is based on three representative glaciers (Storbreen, Hellstugubreen and Gråsubreen) that were synthesized into one composite record which we term 'Gjennomsnittsbreen' ('mean glacier' in Norwegian) to filter out localized controls on the behaviour of individual glaciers. While not ignoring the role of precipitation on glacier mass balance, our reconstruction demonstrates that glaciers in this region exhibit a strong summer temperature control and appear to have been declining more or less continuously since the mid‐18th century. However, it also shows that this long‐term trend of overall retreat in Jotunheimen is punctuated by relatively short‐lived periods of neutral or occasionally positive glacier mass balance, signifying periods of stillstand or small‐scale glacier advance. These periods or 'events' in our reconstruction were compared with an independent record of 12 moraine‐building events developed using lichenometry. A minimum of 10 of the moraine‐building events identifiable in our reconstruction were also identifiable in the lichenometric data which affords confidence in the performance of our interrogative model. A critical implication of this successful glacier mass balance reconstruction based on just summer temperature is that for Jotunheimen – in contrast to Norwegian maritime glaciers further to the west – there is no need (as was proposed in some previous studies) to invoke large, prolonged increases in winter snowfall to explain glacier advances, not even for events such as the Little Ice Age.